Institutional core facilities: prerequisite for breakthroughs in the life sciences: Core facilities play an increasingly important role in biomedical research by providing scientists access to sophisticated technology and expertise. (13th July 2016) - Meder, Doris; Morales, Mònica; Pepperkok, Rainer; Schlapbach, Ralph; Tiran, Andreas; Van Minnebruggen, Geert
Abstract : Core facilities have become an important resource in biomedical research, providing scientists with access to sophisticated instrumentation and expertise. To enable scientists to perform ever more complex and difficult experiments, core facilities not only need to constantly upgrade technology and expertise, but also cooperate and pool their assets.